Perception of Justice and Employees’ Brand-Based Equity in the Service Sector: Evidence From Education Industry - Li, Lu (Frontiers in Psychology, 2022)
This study aims to investigate the impact of justice perception of the employees on three dimensions of employee-based brand equity (EBBE) under the mediating role of psychological contract fulfillment. For this purpose, data have been collected from the employees of the education industry under the convenience sampling technique. In this regard, a survey method was used, and questionnaires were distributed among 420 respondents, out of which 310 questionnaires were received back, and after discarding 32 partially filled questionnaires, useable responses were left (279 observations). Data have been analyzed through structural equation modeling, and the partial least square (PLS)-SEM approach has been used in this regard through the Smart PLS software. Measurement and structural models were assessed, and all the indicators of reliability and validity have been found to be fit. Path estimation indicates that perception of justice promotes brand endorsement and brand allegiance, while the relationship of perception of justice and brand-consistent behavior has not been found statistically significant. Moreover, it has also been found that perception of justice ensures employees that their psychological contract has been met. In addition, psychological contract fulfillment has found a mediating mechanism between the perception of justice and the three dimensions of EBBE.